2022
DOI: 10.1002/anie.202210312
|View full text |Cite
|
Sign up to set email alerts
|

Dearomative Aminocarbonylation of Arenes via Bifunctional Coordination to Chromium

Abstract: Amides are ubiquitous in physical and life sciences. Given the significant abundance of arenes, dearomative aminocarbonylation of arenes would lead to a large and underexplored chemical space for amide discovery. However, such reactions are challenging due to the high degree of resonance stabilization and selectivity issues. Herein, we disclose an unprecedented dearomative trifluoromethylative aminocarbonylation of arenes via bifunctional coordination to chromium, providing a modular platform for the construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…The high chemoselectivity could be ascribed to the selective and efficient activation of the arene π-bonds via η 6 -coordination, as well as the appropriate selection of a mild hydride source Ph 3 SiH. A high level of tolerance was also observed to other mono-, disubstituted benzene derivatives possessing diverse functional groups, like acetal group, methoxyl, free hydroxyl, SiMe 3 , and medicinally relevant heterocycles (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The final ketone product 20 was generated from the corresponding unstable vinyl ether product via hydrolysis in situ after the reduction.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The high chemoselectivity could be ascribed to the selective and efficient activation of the arene π-bonds via η 6 -coordination, as well as the appropriate selection of a mild hydride source Ph 3 SiH. A high level of tolerance was also observed to other mono-, disubstituted benzene derivatives possessing diverse functional groups, like acetal group, methoxyl, free hydroxyl, SiMe 3 , and medicinally relevant heterocycles (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The final ketone product 20 was generated from the corresponding unstable vinyl ether product via hydrolysis in situ after the reduction.…”
Section: Resultsmentioning
confidence: 99%
“…First, the possible isomerization from the 1,4‐reduction product (Birch‐type product) into our 1,2‐reduction product under the quenching conditions was excluded (Scheme 4A), which supported the 1,2‐reduction speculation. Based on our recent mechanistic studies on (η 6 ‐arene)Cr(CO) 3 reagents, [15] the η 5 ‐cyclohexadienyl tricarbonylchromium(0) intermediate formed through the nucleophilic addition of hydride to (η 6 ‐biphenyl)Cr(CO) 3 was successfully trapped by the addition of the Togni's reagent, giving the CF 3 ‐stabilized Cr II complex 57 in 58 % yield (Scheme 4B). X‐ray crystallographic analysis of complex 57 [17] indicated that the nucleophilic addition of hydride should attack the ortho position of the aryl substituent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations